Broadband 1T-titanium selenide-based saturable absorbers for solid-state bulk lasers. Issue 43 (19th September 2018) - Yan, Bingzheng; Zhang, Baitao; Nie, Hongkun; Li, Guoru; Sun, Xiaoli; Wang, Yiran; Liu, Junting; Shi, Bingnan; Liu, Shande; He, Jingliang
Abstract : 1T-titanium selenide (1T-TiSe2 ), a representative of 1T phase transition metal dichalcogenides (TMDs), exhibits semimetallic behaviour with a nearly zero bandgap structure, which makes it a promising photoelectric material. Abstract : 1T-titanium selenide (1T-TiSe2 ), a representative of 1T phase transition metal dichalcogenides (TMDs), exhibits semimetallic behaviour with a nearly zero bandgap structure, which makes it a promising photoelectric material. A high-quality multilayer 1T-TiSe2 saturable absorber (SA) is successfully fabricated by a combination of liquid phase exfoliation and the spin coating method. The broadband nonlinear saturable absorption properties of the prepared 1T-TiSe2 SA are investigated by using the open aperture (OA) Z -scan method. Passively Q-switched (PQS) all-solid-state lasers with different bulk crystals at the wavelengths of 1.0, 1.3, 2.0 and 2.8 μm are realised based on the 1T-TiSe2 SA. To the best of our knowledge, this is the first presentation of the application of a 1T-TiSe2 material to all-solid-state bulk lasers. The results indicate that 1T-TiSe2 could be an alternative broadband SA for solid-state pulsed lasers and exhibits promising potential applications in mode-locked ultrafast lasers.